Depression in Patients with Lung Cancer during the COVID-19 Pandemic - Afladhia, Hanna Lianti; Andarini, Sita (Jurnal Respirasi, 2025)
Introduction: The coronavirus disease (COVID-19) pandemic has caused significant disruptions in various aspects of life, leading to psychological distress and an increase in mental health disorders, particularly in vulnerable populations such as lung cancer patients. This study investigated the depression levels among lung cancer patients during the COVID-19 pandemic. Methods: A cross-sectional study was conducted at the Thoracic Oncology Outpatient Clinic of Persahabatan National Respiratory Referral Hospital, Jakarta. Depression levels were evaluated using the Patient Health Questionnaire-9 (PHQ-9) in Indonesian. Sociodemographic and clinical characteristics and COVID-19-related stress factors (such as concerns about treatment delays, access to healthcare, psychological pressure, and interpersonal relationships) were also assessed. Results: Out of 42 patients, 42.9% were found to have depression during the pandemic. Factors significantly associated with depression included being female, having a lower economic status, poor performance status, undergoing chemotherapy, and experiencing higher levels of psychological pressure related to COVID-19. Conclusion: This study highlighted a high prevalence of depression among lung cancer patients during the COVID-19 pandemic. Psychological assessment and interventions are crucial to prevent further deterioration in mental health and quality of life, which could negatively affect patients' prognoses.